Plants in Caucasian ritual bread traditions: An ethnobotanical and etymological study - Chotalishvili, Lela; Akhvlediani, Nargiz (Ethnobotany Research and Applications, 2026)
Background: The Caucasus maintains rich ethnobotanical traditions where plants play central roles in religious and ritual practices. In recent decades, however, much of this traditional knowledge has been lost. While medicinal and food plants have been studied, the ritual significance of plants in food preparation and etymological connections between vernacular plant names and ancient religious practices remain unexplored. This study examines plant use in ritual bread traditions across three Caucasian regions. Methods: The research is based on semi-structured interviews and participant observation conducted in 2024-2025 in three geographical regions of the Caucasus: Svaneti, the Pankisi Gorge, and the Adjara-Kobuleti region. Plants mentioned by informants were identified in collaboration with local populations, linguists, and botanical experts. Etymological analysis was conducted using comparative-linguistic methods and published etymological dictionaries. Results: Three ritual bread traditions were documented: Svan kut-lemzir, Kist ch'aabilg, and Adjaran sisamiani khach'ap'uri. In these traditions, plants serve not only as culinary ingredients for fermentation and aromatization but also as essential ritual elements. The study focuses on three plants − kut-k'vakh (Plantago major L., Plantago lanceolata L.), kho (Humulus lupulus L.), and sisami (Nigella sativa L.) − revealing how botanical knowledge, linguistic terms, and ritual practice are connected. Their vernacular names reflect Proto-Iranian, pre-Greek, and Kartvelian roots associated with ancient religious practices. Conclusions: Ritual bread-baking traditions remain vibrant − families continue to pass down both the practical techniques and the ritual knowledge. Plant names carry cultural memory of pre-Christian practices and cross-cultural contact. Documenting these traditions helps preserve cultural heritage and the diversity of local plant uses. Future research should expand to other Caucasian regions. Keywords: Caucasus, ethnobotany, ritual bread, traditional knowledge, plant name etymology.